Cornelia Lüdecke, Germans in the Antarctic - Elisasson, Pär (Umeå University Library, 2022)
Review of: Cornelia Lüdecke, Germans in the Antarctic, Cham: Springer Nature Switzerland AG 2021, ISBN 9783030409234, 302 pp; eBook at https://doi.org/10.1007/978-3-030-40924-1. (Translated from the German language edition Deutsche in der Antarktis, Berlin: Christoph Links Verlag GmbH 2015.)